Self-efficacy of healthcare students in disaster preparedness and response: A descriptive study - Al Maliki, Ali Hassan; Al Karbalaei, Zahra Ahmed; Al Samarrai, Mustaga Jassim (Indonesian Journal of Health Services, 2025)
Background: Disasters present significant global health challenges, demanding well-prepared healthcare professionals with strong self-efficacy in preparedness and response. Previous studies highlight gaps between theoretical knowledge and practical readiness, underscoring the need to evaluate disaster response self-efficacy among healthcare students. Objective: This study aimed to assess the self-efficacy of healthcare students in disaster preparedness and response and to identify factors influencing their confidence in managing disaster situations. Methods: A descriptive cross-sectional design was employed among 312 healthcare students from nursing, medical, and allied health programs. Data were collected using a structured questionnaire that included demographic information and the validated Disaster Response Self-Efficacy Scale. Descriptive statistics summarized the data, while inferential analyses, including t-tests, ANOVA, and regression, identified differences and predictors of self-efficacy. Ethical approval was obtained, and informed consent was secured from all participants. Results: The overall mean score of disaster response self-efficacy was moderate (3.41 ± 0.75). Preparedness and knowledge scored highest, while coordination and leadership scored lowest. Significant differences were found across disciplines, with nursing students reporting higher self-efficacy than allied health students. Gender differences indicated that male students were more confident in leadership-related domains. Regression analysis revealed that academic year, prior disaster-related training, and participation in simulation exercises were strong predictors of self-efficacy. Conclusion: Healthcare students possess adequate theoretical knowledge but remain limited in practical disaster readiness, particularly in coordination and leadership. Academic progression and experiential learning enhance self-efficacy, while gender disparities reflect socio-cultural influences.